PENATAAN MANAJEMEN OPERASIONAL KOPERASI SEBAGAI MITRA USAHA KREATIF MASYARAKAT - SAMUEL TENANG UKUR ARDIANTA GINTING,; CONIE NOPINDA BR SITEPU, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Co-operative is one of the efforts as well as the people's economic movement, where the cooperative is a group of people who have a lower level economy, through cooperatives together and want or have a purpose to improve their welfare. Over time the cooperative is not only a collection of people who are economically weak but also belong to those whose economic rate is already high, this can be seen from the problems faced today, the public's view of trust in the Cooperative in becoming a benchmark society to improve living standards began to fall. The number of cooperatives that are tame and do not have a commitment to the purpose of cooperatives actually makes the cooperative including financial institutions that can no longer be trusted. This research is focused on the existence of cooperatives in the community, and the village office where the cooperative is founded or domiciled. The cooperative is notabene as a family-based financial institution, which helps members of the community who are based in the form of operations, which can help to increase or develop the business owned by members who are also customers who become the main lenders. But lately cooperatives prefer oriented businesses as managing partners of funds that go outside of member funds, so that business development is sorted into second, and cooperatives are busy managing grants or assistance from the government, so many cooperatives are closed because they cannot account for the funds and abandon their members.As a result of this study, Table 1 respondent x score obtained stated Agree (S) a number of scores of 80, from 4 villages, and disagreed (TS) a number of scores of 40, with an average score of 60. Table 2 obtained respondent x score stipulated agree (SS) a number of scores of 20, from 4 villages surveyed, and disagreed (R) a number of scores of 60, with an average score of 40. With a result of T = 60 (T > 50 = Positive Attitude). Some cooperatives located in several villages in Patumbak sub-district of Deli Serdang Regency as a place of research are carried out, there are types of cooperatives that run according to operational management in the community, there are forms of loan store cooperatives and all-business cooperatives, and among them have not been able to be hokum due to tax related and have not registered office domicile or do not register their existence in the village office in patumbak sub-district. There needs to be a socialization of the existence of cooperatives in rural areas whose communities are not only in the interest of making loans, but to maintain and avoid losses, as well as protect public money from irresponsible financial institutions.Researchers would like to thank the Ministry of Research and Technology for funding this research, for funding the PDP in 2020, and to the relevant parties so that this research can run as it should.